Rancor: A Gamified Microworld Nuclear Power Plant Simulation for Engineering Psychology Research and Process Control Applications. (September 2017) - Ulrich, Thomas A.; Lew, Roger; Werner, Steffen; Boring, Ronald L.
We demonstrate the development, rationale, and use of a gamified microworld nuclear power plant simulation for engineering psychology research and process control applications. The Rancor microworld was developed to address specific research needs in support of ongoing U.S. nuclear control room modernization efforts. The Rancor microworld serves as a platform for inexpensive cognitive psychology research that would otherwise not be as feasible in typical complex process control research settings. The gamified nuclear power plant simulator is simple enough that untrained, novice participants can quickly learn and control the system. The Rancor microworld is currently configured to support an investigation of attention and situation awareness in nuclear process control is discussed. The Rancor framework is flexible to support rapid modification for addressing research needs related to complex process control.